Pengembangan Website Chatbot Untuk Kampus Bina Darma - Syahrul AlFahryan; Suryayusra Suryayusra (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
The Bina Darma Campus has experienced rapid growth in recent years, resulting in increased complexity in managing various aspects of campus life. One of the problems that arises is the increase in demand for information services and assistance for students. To overcome this challenge, developing a chatbot website is the solution. Chatbots can increase efficiency in providing information and better interaction experiences to users. This research aims to develop a chatbot website that can be used by the Bina Darma Campus. This chatbot is designed to provide information about class schedules, campus facilities, administrative procedures, and other general questions frequently asked by users. The methodology used is the spiral method, which consists of 5 stages, namely planning, analysis, design, implementation, and testing. Then, the chatbot was developed by applying natural language processing technology and integrated with the campus information system. After that, a chatbot trial was carried out with the participation of students. Statistical analysis is used to interpret research results. The research results show that the development of a chatbot website for the Bina Darma Campus was successfully implemented efficiently. Chatbots are able to provide fast and accurate responses to user questions, which then results in a high level of user satisfaction with the experience of interacting with the chatbot. Apart from that, chatbots have also succeeded in reducing the workload of administrative staff in providing routine information to users. These findings indicate that chatbots have the potential to improve the overall efficiency of campus services.